PENGEMBANGAN PERANGKAT PEMBELAJARAN CASE BASED LEARNING DENGAN MEDIA KOMIK DIGITAL - rustina, ratna; Muzdalipah, Ipah; Hidayat, Edi (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2024)
This study aims to develop a mathematics learning device based on Case Based Learning (CBL) integrated with digital comics media for the topic of Systems of Linear Equations in Two Variables (SPLDV) for junior high school students. The method used is Research and Development (RD) with the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Validation involved subject matter experts, media experts, and limited trials with students. The results show that the developed learning device is highly feasible, with an average validation score of 89.2%. The use of digital comics media based on CBL significantly increases students' motivation and conceptual understanding of mathematics, as evidenced by a 24.2% increase in the average SPLDV conceptual understanding score. In conclusion, the integration of the CBL model and digital comics is effective in supporting contextual, innovative, and adaptive mathematics learning in the digital eraKeywords:    Case Based Learning; digital comics; conceptual understanding; mathematics education; instructional innovation.